Artificial intelligence : why and how it is revolutionizing healthcare management - Buijs, Elvira; Maggioni, Elena; Mazziotta, Francesco; Carrafiello, Gianpaolo; Lega, Federico (European health management in transition., 2024)
Artificial intelligence (AI) has the potential to drastically change healthcare, including the optimisation of time and materials for clinical tasks (efficiency), and more accurate diagnose detection (effectiveness). However, these clinical-based AI applications are still in very early development stages. Investigating the wide range of applications of AI in both community and hospital care settings, and along the patient care pathway, the chapters here focus on applications capable of contributing to the workflow and management of the activities to be provided. The impact of AI in solving the main issues of modern medicine is discussed, such as reorganization of services towards patient-centricity, management of task shifting and skills mix, greater competitiveness between public and private sector, and financing mechanisms. Difficulties that may arise during the implementation of AI in an organization are addressed, including practical solutions, providing a practical guide for managers, clinical leaders and policy makers. Artificial Intelligence: Why and How it is Revolutionizing Healthcare Management identifies a roadmap for the appropriate introduction of artificial intelligence in healthcare organizations that responds to the need of decision-makers and managers to have a clear picture of how to move in the developing field of AI.